Get the most out of your questions with the extensive resources available on IDNLearn.com. Our platform offers reliable and comprehensive answers to help you make informed decisions quickly and easily.
Sagot :
Answer:
PLEASE MARK ME AS BRANLIEST!!!!!
Step-by-step explanation:
a1 = first term; an= an-1 + d a1 = the first term in the sequence an = the nth term in the sequence an-1 = the term before the nth term n = the term number d = the common difference.
{10, 15, 20, 25, 30, 35, } first term = 10, common difference = 5 recursive formula: a1= 10; an= an-1 + 5
f(n) = f(n-1) + 12
f(1) = 7
f(2) = (7-1) + 12 = 18
f(3) = (18-1) + 12 = 29
f(4) = (29-1) + 12 = 40
f(5) = (40-1) + 12 = 51
7, 18, 29, 40, 51
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your search for answers ends at IDNLearn.com. Thanks for visiting, and we look forward to helping you again soon.